2013
DOI: 10.1371/journal.pone.0069209
|View full text |Cite|
|
Sign up to set email alerts
|

Nbn and Atm Cooperate in a Tissue and Developmental Stage-Specific Manner to Prevent Double Strand Breaks and Apoptosis in Developing Brain and Eye

Abstract: Nibrin (NBN or NBS1) and ATM are key factors for DNA Double Strand Break (DSB) signaling and repair. Mutations in NBN or ATM result in Nijmegen Breakage Syndrome and Ataxia telangiectasia. These syndromes share common features such as radiosensitivity, neurological developmental defects and cancer predisposition. However, the functional synergy of Nbn and Atm in different tissues and developmental stages is not yet understood. Here, we show in vivo consequences of conditional inactivation of both genes in neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 63 publications
0
23
1
Order By: Relevance
“…However, ActCasp3 was negative indicating that the cell death is caspase-3 independent. Given that inactivation of DSBs repair genes in PC does not cause any defects, 38 and the fact that γ-H2AX-positive PC are few compared with those exhibiting Golgi fragmentation and p62 accumulation, we suggest that Rint1 deficiency triggered neurodegeneration in vivo is not a secondary result of genomic instability. It supports a direct role for Rint1 in ER-Golgi homeostasis and autophagy, and highlights the complexity and the variety of pathways in which Rint1 is involved.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…However, ActCasp3 was negative indicating that the cell death is caspase-3 independent. Given that inactivation of DSBs repair genes in PC does not cause any defects, 38 and the fact that γ-H2AX-positive PC are few compared with those exhibiting Golgi fragmentation and p62 accumulation, we suggest that Rint1 deficiency triggered neurodegeneration in vivo is not a secondary result of genomic instability. It supports a direct role for Rint1 in ER-Golgi homeostasis and autophagy, and highlights the complexity and the variety of pathways in which Rint1 is involved.…”
Section: Resultsmentioning
confidence: 81%
“…Anaphase bridges are found among cells exhibiting impaired telomere homeostasis [39][40][41][42] and defective DNA DSB repair. [36][37][38][39][40][41][42][43][44][45][46][47][48][49] RINT1 is known to be involved in both pathways through interaction with p130 15 or Rad50. 14 The structure of chromosome fusion in the Rint1-deficient cells supports the hypothesis of defective DSB repair (Figures 4c and d).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, only lens fiber cells destroy nuclei within the cell. Despite many investigations over the past century, the molecular mechanism(s) by which fiber cell denucleation occurs has remained a mystery (Vrensen et al, 1991(Vrensen et al, , 2004He et al, 1998He et al, , 2010Ivanov et al, 2005;Xie et al, 2007;Rivera et al, 2009;Wang et al, 2010;Gupta et al, 2011;Ma et al, 2011;Jarrin et al, 2012;Rodrigues et al, 2013). Preliminary work suggested that the lens 'appropriates' normal mitotic mechanisms in order to accomplish denucleation: specifically, that nuclear membrane disassembly occurs after phosphorylation of nuclear lamins and that stabilization of the CDK1 inhibitor p27 KIP1 delays denucleation (Caceres et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA damage response has been well-characterized [36], and the importance of several of these genes in mouse neural development has been described [31, 37-40]. The commonality of these mouse models lies in their hypomorphic cerebellum, which lacks its characteristic lamination and foliation.…”
Section: Discussionmentioning
confidence: 99%